IMPLEMENTASI METODE TILAWATI UNTUK MENUMBUHKAN KEPERCAYAAN DIRI DALAM MEMBACA DAN MENGHAFAL AL-QUR’AN PADA SISWA KELAS 1 MINU HIDAYATUN NAJAH TAHUN PELAJARAN 2025/2026 - Arjuna Arantisi; M. Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by low level of self-confidence among first-grade students in reading and memorizing the Qur’an, particularly when required to perform individually in front of class. This condition is influenced by students’ early age, uneven mastery of basic Arabic letters, and feelings of shyness or fear of making mistakes. Therefore, an instructional method is needed that not only emphasizes accuracy and fluency in recitation but also supports students’ affective development. This research aims to outline application of Tilawati method and examine how it contributes to strengthening self-confidence among first-grade learners at MI NU Hidayatun Najah in the 2025/2026 academic year. A descriptive qualitative design was employed in this study. The research participants consisted of the Al-Qur’an instructor along with all students in the first grade. Information was gathered through participatory classroom observation, comprehensive interviews with the teacher and selected pupils, and documentation covering learning activities and students’ progress records. The analytical process followed several stages, namely organizing and reducing the collected data, presenting the findings, and formulating conclusions. To strengthen the credibility of the results, triangulation of both data sources and research methods was applied. The findings indicate that the Tilawati method was implemented systematically through classical and individual instruction using a structured read-and-listen technique combined with the rost melody and gradual repetition. The teacher acted as both a recitation model and motivator by providing positive reinforcement. The implementation created an engaging, structured, and supportive learning environment that encouraged students to participate actively and confidently. As a result, students demonstrated noticeable improvement in their courage, participation, recitation fluency, memorization skills, and self-confidence when performing in front of their peers. Thus, the Tilawati method is considered effective in developing both cognitive and affective aspects of students at the elementary madrasah level.